PENGARUH PERBEDAAN UKURAN MATA PANCING TERHADAP HASIL TANGKAPAN NELAYAN PANCING ULUR DESA MOLAMAHU KECAMATAN PAGUAT KABUPATEN POHUWATO - Salam, Aziz; Husain, Ratmin; Nursinar, Sitti (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2024)
This research aims to determine the highest number of fish catches based on the size of the hook in the operation of hand-line fishing gear and to determine the effect of differences in the size of the hook on the catch of hand-line fishermen in Molamahu Village, Paguat District, Pohuwato Regency. This research was carried out from June 2019 to January 2020. The method used in this research was experimental fishing. Observations were carried out 15 times, each trip was divided into 3 boats, using a Completely Randomized Design (CRD), data analysis using the data normality test (Liliefors test), homogeneity test using the barlet test, hypothesis testing (one way anova) and the BNT follow-up test ( Smallest Real Difference). The results of the research show that all types of fishermen's catches amounted to 9 families of coral fish, where fishing hook No. 17 obtained more catches (as many as 432 heads) compared to hook No. 10, No. 14 and No. 20. The results of the BNT test analysis show that, the comparison of the number of catches between hook No. 17 and No. 20; between no. 17 and no 14; between No. 17 and No. 10; between No. 20 and No. 14; between No. 20 and No. 10; and between no.14 and No. 10 are all at obvious different.